Deep brain stimulation effects on verbal fluency dissociated by target and active contact location - John, Kevin D. (Ann Clin Transl Neurol, 2021)
OBJECTIVE: Deep brain stimulation (DBS) improves motor symptoms in Parkinson’s disease (PD), but it can also disrupt verbal fluency with significant costs to quality of life. The current study investigated how variability of bilateral active electrode coordinates along the superior/inferior, anterior/posterior, and lateral/medial axes in the subthalamic nucleus (STN) or the globus pallidus interna (GPi) contribute to changes in verbal fluency. We predicted that electrode location in the left hemisphere would be linked to changes in fluency, especially in the STN. METHODS: Forty PD participants treated with bilateral DBS targeting STN (n = 23) or GPi (n = 17) completed verbal fluency testing in their optimally treated state before and after DBS therapy. Normalized atlas coordinates from left and right active electrode positions along superior/inferior, anterior/posterior, and lateral/medial axes were used to predict changes in fluency postoperatively, separately for patients with STN and GPi targets. RESULTS: Consistent with prior studies, fluency significantly declined pre‐ to postsurgery (in both DBS targets). In STN‐DBS patients, electrode position along the inferior to superior axis in the left STN was a significant predictor of fluency changes; relatively more superior left active electrode was associated with the largest fluency declines in STN. Electrode coordinates in right STN or GPi (left or right) did not predict fluency changes. INTERPRETATION: We discuss these findings in light of putative mechanisms and potential clinical impact.